Foliicolous fungi from North–Eastern terai belt of U.P.: Some new taxa of anamorphic powdery mildews - KAMAL* and NASIM AHMAD, VIVEK KUMAR PAL, MASOOD AKHTAR (Indian Phytopathology, 2006)
Three new taxa of anamorphic powdery mildews viz., Oidium capparidacearum, O. pergulariae and O. spilanthedis collected from the forest flora of terai belt of North-Eastern Uttar Pradesh are described and illustrated.